Biermann interpolation of Birkhoff type - Marius Birou (Journal of Numerical Analysis and Approximation Theory, 2005)
If \(P_{0},P_{1},...,P_{r}\) and \(Q_{0},Q_{1},...,Q_{r}\) are Birkhoff univariate projectors which form the chains\[P_{0}\le P_{1}\le\dots\le P_{r},\quad Q_{0}\le Q_{1}\le\dots\le Q_{r},\]we can define the Biermann operator of Birkhoff type\[B_{r}^{B}=P_{0}^{\prime}Q_{r}^{\prime\prime}\oplus P_{1}^{\prime}Q_{r-1}^{\prime\prime}\oplus\dots\oplus P_{r}^{\prime}Q_{0}^{\prime\prime},\]where \(P_{1}^{\prime},\dots,P_{r}^{\prime}\),\(Q_{1}^{\prime\prime},\dots ,Q_{r}^{\prime\prime}\) are the parametric extension. We give the representations of Biermann interpolant of Birkhoff type for two particular cases (Abel-Goncharov and Lidstone projectors) and we calculate the approximation order of Biermann interpolant in these cases.